Information visualization system - Rusu, Adrian; Santiago, Confesor (2011)
A Web browsing and visualization system and method wherein: (i) Web data is retrieved and displayed in real-time (i.e., Web data is not pre-recorded), (ii) browsing and visualization are synchronized together in the same interface, (iii) a tree-based, rings-type visualization engine, (iv) space-efficient display of visualization, and (v) the amount of resources needed from the host computer is comparatively modest. In addition, the tree-based rings engine used to create the visualization displays the information in a smaller area than previous systems. Thus, the system requires less screen space to display the same amount of information as comparable systems. Alternatively, it can display more information to the user in the same amount of screen space as comparable systems. Moreover, although the present invention is disclosed herein in connection with visualizing Web data, it can be applied to portray any information hierarchy.